Analysis of the Effect of Brand Image, Product Quality, and Price Perception on Consumer Purchase Decisions for Toyota Avanza PT. Hasjrat Abadi Manado during PPnBM policy - Rexzy Yehuda Zakawerus; Lisbeth Mananeke; Willem JFA Tumbuan (International Journal on Economics, Finance and Sustainable Development, 2022)
This study aims to test and analyze whether brand image, product quality, and price perception have a simultaneous and partial effect on consumer purchasing decisions for Toyota Avanza PT. Hasjrat Abadi Manado during the PPnBM policy. As respondents, 97 respondents were buyers of Toyota Avanza cars from March 2021 to August 2021. This study uses the analysis method of validity and reliability testing, classical assumption test, hypothesis testing, multiple linear and regression, and coefficient of determination test. This study found that simultaneously or simultaneously brand image, product quality, and price perception affect consumer purchasing decisions for Toyota Avanza during the PPnBM policy. Separately or partially only brand image has no effect on consumer purchasing decisions. Therefore, the Toyota Avanza brand image must continue to be improved even though it is well known.